Modified activated carbon material as well as preparation method and application thereof

By introducing oxygen-containing functional groups and methyl acrylate oligomers on the surface of activated carbon, the modified activated carbon material solves the problems of small adsorption capacity and poor selectivity of acrylate VOC in the prior art, and achieves an efficient acrylate VOC removal effect.

CN119549127APending Publication Date: 2025-03-04WUHAN UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411275022.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing activated carbon materials have small adsorption capacity and poor selectivity to acrylate VOCs, making it difficult to meet the needs of efficient removal.

Method used

By introducing oxygen-containing functional groups and methyl acrylate oligomers on the surface of the activated carbon, the activated carbon material is modified to enhance its adsorption selectivity and adsorption ability to acrylate-based VOCs.

Benefits of technology

It significantly improves the adsorption capacity and selectivity of modified activated carbon materials to acrylate VOCs, and is suitable for efficient removal of a variety of acrylate VOCs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549127A_ABST
    Figure CN119549127A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorption materials, and discloses a modified activated carbon material and a preparation method and application thereof.The preparation method comprises the following steps that 1, an oxidizing agent solution is added into cleaned and dried activated carbon, heating modification is conducted, then the activated carbon is taken out, the oxidizing agent solution and impurities remaining in pores of the activated carbon are removed through washing, and drying is conducted to obtain modified activated carbon; pre-treated activated carbon is obtained; and 2) placing the pretreated activated carbon in a methyl acrylate atmosphere, then taking out the pretreated activated carbon, spraying a photoinitiator solution on the surface of the pretreated activated carbon, carrying out ultraviolet irradiation, and drying after the irradiation is finished to obtain the modified activated carbon material. According to the invention, the oxygen-containing functional group and the methyl acrylate oligomer are introduced on the surface of the activated carbon, so that the adsorption selectivity and the adsorption capacity on the acrylate VOC are enhanced, and the modified activated carbon material is suitable for efficient removal of various acrylate VOCs and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption materials, and specifically relates to a modified activated carbon material and a preparation method and application thereof. Background Art

[0002] The rapid development of industrialization and urbanization has brought about an increasingly serious impact on human health caused by volatile organic compounds (VOCs). Acrylic esters, as an important monomer for the synthesis of polymer materials, have important applications in coatings, adhesives, and even 3D printing. However, acrylate VOCs also cause environmental pollution and harm to human health. In recent years, there have been many methods for treating VOCs, such as catalytic oxidation, condensation, and adsorption.

[0003] Catalytic oxidation is an effective waste gas treatment technology. It uses heating to make VOCs undergo oxidation reactions under the action of catalysts and convert them into harmless carbon dioxide and water. Although this method performs well in treating VOCs, the equipment investment cost and operating costs are very high. The condensation method uses the property that different substances have different saturated vapor pressures at different temperatures to condense VOCs in a gaseous state by lowering the system temperature or increasing the system pressure, and separates them from the mixed gas. However, its operation is difficult and has strict requirements on conditions, which limits its application to a certain extent.

[0004] In contrast, the adsorption method has great advantages in terms of technology due to its simple equipment, convenient operation, and easy control. Activated carbon has become a commonly used adsorption material in industry due to its good adsorption performance and low price, but its adsorption capacity for acrylate VOC is small and its adsorption selectivity is poor, which makes it difficult to meet the demand for efficient removal of acrylate VOC. Therefore, it is necessary to develop a modified activated carbon material for the adsorption of acrylate VOC. Summary of the invention

[0005] The technical problem to be solved by the present invention is to address the deficiencies in the prior art and provide a modified activated carbon material and a preparation method and application thereof. By introducing oxygen-containing functional groups and methyl acrylate oligomers on the surface of activated carbon, the adsorption selectivity and adsorption capacity for acrylate VOCs are enhanced. The modified activated carbon material is suitable for the efficient removal of a variety of acrylate VOCs and has broad application prospects.

[0006] In order to solve the technical problem proposed by the present invention, the present invention provides a method for preparing a modified activated carbon material, comprising the following steps:

[0007] 1) adding an oxidant solution to the cleaned and dried activated carbon, heating for modification, then taking it out, washing to remove the oxidant solution and impurities remaining in the pores of the activated carbon, and drying to obtain pretreated activated carbon;

[0008] 2) placing the pretreated activated carbon in a methyl acrylate atmosphere, then taking it out, spraying the surface with a photoinitiator solution, and then irradiating it with ultraviolet light. After the irradiation, drying is performed to obtain a modified activated carbon material.

[0009] In the above scheme, the activated carbon is a coal-based columnar activated carbon with a diameter of 1.3 to 2 mm, a length of 2 to 5 mm, and a BET specific surface area of ​​900 to 1100 m 2 / g, total pore volume is 0.47~0.53cm 3 / g, and the average pore size is 2.7~2.9nm.

[0010] In the above scheme, the oxidant solution is an ammonium persulfate solution with a concentration of 0.1 to 2 mol / L.

[0011] In the above scheme, the volume ratio of the activated carbon mass to the oxidant solution is (2-3.5) g:10 mL.

[0012] In the above scheme, the heating temperature of the heating modification is 60-70° C., and the modification time is 2-3 hours.

[0013] In the above scheme, the heating modification is carried out under stirring conditions, and the stirring rate is 150 to 300 r / min.

[0014] In the above scheme, the concentration of methyl acrylate in the methyl acrylate atmosphere is 30 to 300 mg / L, the atmosphere temperature is 20 to 30° C., and the standing time is 10 to 30 min.

[0015] In the above scheme, the photoinitiator solution is a mixed solution of photoinitiator TPO and photoinitiator 819, and the total concentration is 1 to 5 mg / mL.

[0016] Furthermore, in the photoinitiator solution, the mass ratio of photoinitiator TPO to photoinitiator 819 is (1-3):1.

[0017] In the above scheme, the volume ratio of the mass of the pretreated activated carbon to the photoinitiator solution is 30g:(1-3)mL.

[0018] In the above scheme, the wavelength of the ultraviolet irradiation is 300-400nm, the power is 5-10W, and the irradiation time is 5-60min.

[0019] In the above scheme, the drying is all forced air drying, the drying temperature is 100-110° C., and the drying time is 4-24 hours.

[0020] The present invention also provides a modified activated carbon material, which is prepared by the above preparation method.

[0021] In the above scheme, the BET specific surface area of ​​the modified activated carbon material is 1000-1200m 2 / g, total pore volume is 0.58~0.65cm 3 / g, and the average pore size is 2.3-2.5nm.

[0022] The present invention also provides an application of a modified activated carbon material in the adsorption of acrylate VOCs. The application method is: loading the modified activated carbon material into a reactor, passing gas into the reactor, and the modified activated carbon material adsorbs acrylate VOCs in the gas.

[0023] In the above scheme, the acrylic ester VOC includes one or more of methyl acrylate, methyl methacrylate, and butyl acrylate.

[0024] In the above scheme, the concentration of acrylic acid ester VOC in the gas is 20-50 mg / m 3 .

[0025] In the above scheme, the adsorption is carried out at normal pressure and a temperature of 20 to 30°C.

[0026] In the above scheme, the adsorption capacity of the modified activated carbon material for acrylic ester VOC is 150 to 400 mg / g.

[0027] The technical concept and technical principle of the present invention are:

[0028] The invention is based on the demand of improving the adsorption capacity and selectivity of activated carbon for acrylate VOC. Firstly, the activated carbon is modified by using an ammonium persulfate solution, polar groups such as carboxyl groups are introduced on the surface of the activated carbon, the pore volume is widened, and the specific surface area is increased; secondly, methyl acrylate is introduced on the surface of the activated carbon by an atmosphere method, and due to the effect of the previous modification, the pore structure of the activated carbon will not be blocked during this introduction; then, a photoinitiator is sprayed, and the residual persulfate radicals on the surface of the activated carbon can also be used as an auxiliary initiator, and methyl acrylate is fixed on the surface of the activated carbon in the form of oligomers through photocuring, so that the surface of the final modified activated carbon material has both oxygen-containing functional groups and methyl acrylate oligomers.

[0029] When the modified activated carbon material is used to adsorb acrylate VOCs, the inductive dipoles of the oxygen-containing groups on the surface can produce an inductive effect with the charge on the acrylate VOCs, and quickly adsorb the acrylate VOC gas; while the methyl acrylate oligomers on the surface show a strong similar attraction to acrylate VOCs, which improves the adsorption selectivity. This may be because the charge distribution of the methyl acrylate oligomers makes its methoxy end show a positive potential, which is more inclined to produce charge attraction to the unsaturated bonds of acrylate VOCs. At the same time, due to the electron-withdrawing effect of the carbonyl group in methyl acrylate, there is a conjugation effect between the double bond and the carbonyl group, and the π electrons on the double bond are biased towards the carbonyl group, making the remote carbon atom positively charged. However, for substances with longer alkane ends such as butyl acrylate, the alkane end is an electron-donating group and is electronegative, so there is charge attraction. Therefore, the combined effect of oxygen-containing functional groups and methyl acrylate oligomers significantly enhances the adsorption capacity of acrylate VOCs.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention modifies activated carbon, introduces oxygen-containing functional groups and methyl acrylate oligomers on the surface of the activated carbon, significantly enhances the adsorption selectivity and adsorption capacity for acrylate VOCs, and is suitable for the efficient removal of various acrylate VOCs; the modification process of the present invention is simple and has a short cycle, while improving the adsorption performance of activated carbon for acrylate VOCs, the economic advantage of activated carbon is retained; therefore, the modified activated carbon material of the present invention is an ideal choice for the adsorption of acrylate VOCs and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a physical picture of the modified activated carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0034] In the following examples, the activated carbon used is coal-based columnar activated carbon, which has a diameter of 1.8 to 2.0 mm, a length of 4 to 5 mm, and a specific surface area of ​​900 to 1000 m 2 / g, total pore volume is 0.49~0.53cm 3 / g, and the average pore size is 2.7-2.8nm.

[0035] Example 1

[0036] A method for preparing a modified activated carbon material comprises the following steps:

[0037] 1) Place the activated carbon in distilled water and ultrasonically clean it for 5 minutes, repeat 3 times, and then put it into a blast drying oven at 100°C for 4 hours; prepare a 0.1 mol / L ammonium persulfate solution with a 0.5 mol / L sulfuric acid solution as a solvent; put the cleaned and dried activated carbon into a three-necked flask, add the ammonium persulfate solution, the volume ratio of the activated carbon mass to the ammonium persulfate solution is 3g:10mL, shake it evenly, cover it with a glass stopper, put it into a constant temperature water bath, and modify it at 60°C and 200r / min stirring conditions for 2 hours; take it out, shake it with distilled water at 25°C and 150rpm to remove the oxidant solution and impurities remaining in the pores of the activated carbon, repeat the washing several times until the pH of the upper liquid is neutral, and put it into a blast drying oven at 100°C for 12 hours to obtain pretreated activated carbon;

[0038] 2) The pretreated activated carbon was placed in a methyl acrylate atmosphere with a concentration of 30 mg / L and an atmosphere temperature of 25°C. After being placed for 20 minutes, it was taken out and a photoinitiator solution was sprayed on the surface. The photoinitiator solution was a mixed solution of photoinitiator TPO and photoinitiator 819 with a total concentration of 1 mg / mL, wherein the mass ratio of TPO to 819 was 1:1, and the volume ratio of the mass of the pretreated activated carbon to the photoinitiator solution was 30 g:1 mL. Then, an ultraviolet lamp was used for irradiation. The wavelength of the ultraviolet lamp was 365 nm, the power was 6 W, and the irradiation was performed for 5 minutes. After the irradiation, it was placed in a forced air drying oven and dried at 100°C for 12 hours to obtain a modified activated carbon material.

[0039] Figure 1 This is a physical picture of the modified activated carbon material prepared in Example 1. It can be seen from the figure that the activated carbon is in the shape of a black column, has a complete structure and no impurities on the surface, and the modification process does not damage the overall structure of the activated carbon.

[0040] Example 2

[0041] A method for preparing a modified activated carbon material comprises the following steps:

[0042] 1) Place the activated carbon in distilled water and ultrasonically clean it for 5 minutes, repeat 3 times, and then put it into a blast drying oven at 105°C to dry it for 5 hours; use 0.5mol / L sulfuric acid solution as a solvent to prepare 0.5mol / L ammonium persulfate solution; put the cleaned and dried activated carbon into a three-necked flask, add the ammonium persulfate solution, the volume ratio of the activated carbon mass to the ammonium persulfate solution is 2g:10mL, shake it evenly, cover it with a glass stopper, put it into a constant temperature water bath, and modify it for 3 hours at 65°C and 150r / min stirring conditions; take it out, wash it with distilled water at 25°C and 150rpm to remove the oxidant solution and impurities remaining in the pores of the activated carbon, repeat the washing several times until the pH of the upper liquid is neutral, and put it into a blast drying oven at 105°C to dry it for 10 hours to obtain pretreated activated carbon;

[0043] 2) The pretreated activated carbon was placed in a methyl acrylate atmosphere with a concentration of 40 mg / L and an atmosphere temperature of 20°C. After being placed for 10 minutes, it was taken out and a photoinitiator solution was sprayed on the surface. The photoinitiator solution was a mixed solution of photoinitiator TPO and photoinitiator 819 with a total concentration of 2 mg / mL, wherein the mass ratio of TPO to 819 was 2:1, and the volume ratio of the mass of the pretreated activated carbon to the photoinitiator solution was 30 g:2 mL. Then, an ultraviolet lamp was used for irradiation. The wavelength of the ultraviolet lamp was 365 nm and the power was 5 W. The irradiation was performed for 10 minutes. After the irradiation, the activated carbon was placed in a blast drying oven at 105°C for 10 hours to obtain a modified activated carbon material.

[0044] Example 3

[0045] A method for preparing a modified activated carbon material comprises the following steps:

[0046] 1) Place the activated carbon in distilled water and ultrasonically clean it for 5 minutes, repeat 3 times, and then put it into a blast drying oven at 110°C for 6 hours; prepare a 1.0 mol / L ammonium persulfate solution with a 0.5 mol / L sulfuric acid solution as a solvent; put the cleaned and dried activated carbon into a three-necked flask, add the ammonium persulfate solution, the volume ratio of the activated carbon mass to the ammonium persulfate solution is 3g:10mL, shake it evenly, cover it with a glass stopper, put it into a constant temperature water bath, and modify it at 70°C and 250r / min stirring conditions for 2 hours; take it out, wash it with distilled water at 25°C and 150rpm to remove the oxidant solution and impurities remaining in the pores of the activated carbon, repeat the washing several times until the pH of the upper liquid is neutral, and put it into a blast drying oven at 110°C for 16 hours to obtain pretreated activated carbon;

[0047] 2) The pretreated activated carbon was placed in an atmosphere of methyl acrylate with a concentration of 50 mg / L and an atmosphere temperature of 30°C. After being placed for 30 minutes, it was taken out and a photoinitiator solution was sprayed on the surface. The photoinitiator solution was a mixed solution of photoinitiator TPO and photoinitiator 819 with a total concentration of 3 mg / mL, wherein the mass ratio of TPO to 819 was 3:1, and the volume ratio of the mass of the pretreated activated carbon to the photoinitiator solution was 30 g:3 mL. Then, an ultraviolet lamp was used for irradiation. The wavelength of the ultraviolet lamp was 365 nm and the power was 10 W. The irradiation was performed for 30 minutes. After the irradiation, the activated carbon was placed in a forced air drying oven at 110°C for 24 hours to obtain a modified activated carbon material.

[0048] Comparative Example 1

[0049] The comparative example is untreated coal-based columnar activated carbon.

[0050] Comparative Example 2

[0051] The difference between Comparative Example 2 and Example 1 is that step 2) is omitted and the pretreated activated carbon obtained in step 1) is directly used as the final product.

[0052] Application Examples

[0053] The modified activated carbon materials obtained in each embodiment and the finished products obtained in each comparative example were used for adsorption of acrylate VOCs. The specific steps were as follows: the modified activated carbon materials were loaded into a reactor, and a gas containing methyl acrylate was introduced, wherein the initial concentration of methyl acrylate in the gas was 50 mg / m 3 , adsorption was carried out at normal pressure and 25°C. After adsorption saturation, the acrylic ester substances adsorbed on the surface of the modified activated carbon material were extracted by Soxhlet extraction to calculate the adsorption capacity.

[0054] In addition, the BET specific surface area, pore size, total pore volume, etc. of the modified activated carbon materials obtained in each example and the finished products obtained in each comparative example were measured, and the results are summarized in Table 1.

[0055] Table 1

[0056]

[0057] According to the data in Table 1, by comparing Comparative Example 1 with Comparative Example 2, it can be seen that the specific surface area of ​​the activated carbon after ammonium persulfate pretreatment is increased, the average pore size is reduced, and the total pore volume is increased compared with the original sample, indicating that ammonium persulfate can etch more pore structures on the surface of the activated carbon, and while etching a part of the micropores into mesopores, more mesopores are etched, thereby and the effect of the introduced acidic functional groups, the adsorption capacity of methyl acrylate is greatly improved; by comparing Example 1 with Comparative Example 2, it can be seen that after step 2) after the introduction of methyl acrylate oligomers, the specific surface area, average pore size and total pore volume are all reduced compared with those after ammonium persulfate pretreatment, indicating that methyl acrylate oligomers occupy a part of the pores of the activated carbon, and after this step of treatment, its adsorption capacity for methyl acrylate is significantly enhanced, showing the best adsorption performance.

[0058] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A method for preparing a modified activated carbon material, characterized in that: The following steps are involved: 1) adding an oxidant solution to the cleaned and dried activated carbon, heating for modification, then taking it out, washing to remove the oxidant solution and impurities remaining in the pores of the activated carbon, and drying to obtain pretreated activated carbon; 2) placing the pretreated activated carbon in a methyl acrylate atmosphere, then taking it out, spraying the surface with a photoinitiator solution, and then irradiating it with ultraviolet light. After the irradiation, drying is performed to obtain a modified activated carbon material.

2. The method for preparing the modified activated carbon material according to claim 1, characterized in that: The activated carbon is a coal-based columnar activated carbon with a diameter of 1.3 to 2 mm, a length of 2 to 5 mm, and a BET specific surface area of ​​900 to 1100 m 2 / g.

3. The method for preparing the modified activated carbon material according to claim 1, characterized in that: The oxidant solution is an ammonium persulfate solution with a concentration of 0.1-2 mol / L; the volume ratio of the activated carbon mass to the oxidant solution is (2-3.5) g:10 mL.

4. The method for preparing the modified activated carbon material according to claim 1, characterized in that: The heating temperature of the heating modification is 60-70° C., and the modification time is 2-3 hours; the heating modification is carried out under stirring conditions, and the stirring rate is 150-300 r / min.

5. The method for preparing the modified activated carbon material according to claim 1, characterized in that: The concentration of methyl acrylate in the methyl acrylate atmosphere is 30 to 300 mg / L, the atmosphere temperature is 20 to 30° C., and the placement time is 10 to 30 minutes.

6. The method for preparing the modified activated carbon material according to claim 1, characterized in that: The photoinitiator solution is a mixed solution of photoinitiator TPO and photoinitiator 819, with a total concentration of 1-5 mg / mL, wherein the mass ratio of photoinitiator TPO to photoinitiator 819 is (1-3):

1.

7. The method for preparing the modified activated carbon material according to claim 1, characterized in that: The volume ratio of the mass of the pretreated activated carbon to the photoinitiator solution is 30g:(1-3)mL; the wavelength of the ultraviolet irradiation is 300-400nm, the power is 5-10W, and the irradiation time is 5-60min.

8. A modified activated carbon material prepared by the method according to any one of claims 1 to 7.

9. Use of the modified activated carbon material as claimed in claim 8 in the adsorption of acrylic ester VOCs.

10. The use of the modified activated carbon material according to claim 9 in adsorbing acrylic acid ester VOCs, characterized in that: The acrylic ester VOC includes one or more of methyl acrylate, methyl methacrylate, and butyl acrylate; the adsorption is carried out at normal pressure and a temperature of 20 to 30° C.; the adsorption capacity of the modified activated carbon material for acrylic ester VOC is 150 to 400 mg / g.

Citation Information

Cited By

  • Composite modified biochar, preparation method, application and VOC (volatile organic compound) adsorption device

    CN122187009A

  • A composite modified biochar, its preparation method, its uses, and a VOC adsorption device.

    CN122187009B